STRATEGI GEREJA TORAJA DALAM MENDORONG PERTUMBUHAN UMKM MELALUI MOMENTUM 110 TAHUN IMT SEBAGAI DASAR PEMBERDAYAAN - Abdiel Putra Kapuangan; Abigael Tiku Dualembang, Junairi Yuris Siruru, Ernawati Patiung, Suprianto Sapu' (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the role of the Toraja Church in encouraging the growth of Micro, Small, and Medium Enterprises (MSMEs) by utilizing the momentum of 110 years of the entry of the Gospel into the Land of Toraja (IMT). The research method used is qualitative with a library study approach, collecting data from literature, church documents, and related sources. The formulation of the problem in this study is how the Toraja Church utilizes the momentum of 110 years of IMT to encourage the growth of UMKM, secondly what are the empowerment strategies carried out by the Toraja Church, and how are they relevant to Amartya Sen's capability approach theory?. The objectives of the study include analyzing the role of the Toraja Church in developing UMKM through the momentum of 110 years of IMT, then identifying and evaluating empowerment strategies based on the capability approach perspective, and providing recommendations for optimizing UMKM empowerment programs for the welfare of the Toraja people. The results of the study show that the Toraja Church utilizes the momentum of 110 years of IMT as a platform to increase the capacity of MSMEs through training, mentoring, and access to capital. The empowerment strategy implemented is in line with Amartya Sen's theory, which emphasizes increasing individual capabilities to achieve prosperity. In conclusion, the Toraja Church has a strategic role in empowering MSMEs through a faith-based approach and local wisdom, but stronger synergy with stakeholders is needed to expand the impact of empowerment.